Tissue tension and not interphase cell shape determines cell division orientation in the Drosophila follicular epithelium. (26th November 2018) - Finegan, Tara M; Na, Daxiang; Cammarota, Christian; Skeeters, Austin V; Nádasi, Tamás J; Dawney, Nicole S; Fletcher, Alexander G; Oakes, Patrick W; Bergstralh, Dan T
Abstract: We investigated the cell behaviors that drive morphogenesis of the Drosophila follicular epithelium during expansion and elongation of early‐stage egg chambers. We found that cell division is not required for elongation of the early follicular epithelium, but drives the tissue toward optimal geometric packing. We examined the orientation of cell divisions with respect to the planar tissue axis and found a bias toward the primary direction of tissue expansion. However, interphase cell shapes demonstrate the opposite bias. Hertwig's rule, which holds that cell elongation determines division orientation, is therefore broken in this tissue. This observation cannot be explained by the anisotropic activity of the conserved Pins/Mud spindle‐orienting machinery, which controls division orientation in the apical–basal axis and planar division orientation in other epithelial tissues. Rather, cortical tension at the apical surface translates into planar division orientation in a manner dependent on Canoe/Afadin, which links actomyosin to adherens junctions. These findings demonstrate that division orientation in different axes—apical–basal and planar—is controlled by distinct, independent mechanisms in a proliferating epithelium. Synopsis: Planar division orientation is independent of cell shape cues and spindle‐orienting machinery Mud/Pins in the proliferating Drosophila follicular epithelium. Instead cortical tension at the apical surface translates into division orientation in a manner dependent on Canoe, which links actomyosin to adherens junctions. Inhibition of cell division does not affect growth and elongation of the egg chamber, but interferes with optimal geometric packing of the tissue. Planar division orientation is biased in the direction of tissue expansion, not interphase cell shape. Inhibition of spindle‐orienting machinery (Mud depletion) does not perturb planar spindle orientation in the follicular epithelium. Canoe depletion, which prevents cells from responding to tension, disrupts planar spindle orientation in the follicular epithelium. Abstract : Combination of semi‐automated image analysis and laser ablation experiments reveals that the directional stress associated with tissue elongation determines planar division orientation, rather than long axis of the cell.